The feasibility of integrating form and meaning in the language classroom: A qualitative study of classroom discours Language; Classroom; Qualitative - Pawlak, Mirosław (Glottodidactica, 2005)
Recent years have witnessed a revival of interest in form-focused instruction in foreign language pedagogy and there is a growing realization that a certain degree of emphasis on formal aspects of the target language is necessary if learners are to achieve high levels of accuracy (e.g. Doughty and Williams 1998; Ellis 2001). In the view of second language theorists and researchers, one of the ways in which this kind of emphasis can most profitably be accomplished is by drawing students' attention to linguistic forms as they are engaged in primarily meaning-focused activities (cf. Long and Robinson 1998). Such a dual focus on form and meaning can, for example, result from the provision of explicit or implicit negative feedback targeting the forms that turn out to be problematic. The paper will discuss the findings of a research project which investigated the feasibility of integrating form and meaning during naturally occurring secondary school English lessons. Thirty 45-minute lessons were tape-recorded, parts of the lessons which were largely communicative in nature were identified and transcribed, and the exchanges with a dual focus of the kind described above were pinpointed and subjected to qualitative analysis. The analysis showed that it is in fact possible to integrate form and meaning during communication-focused activities, that focus on form of that kind can be used to address not only grammatical problems but also those related to lexis and phonology, and that it may be beneficial for the learners' interlanguage development.